Profit-Sharing System Between Durian Orchard Cultivators and Landowners in Kedaloman Village From the Perspective of Islamic Economic Law - indra pratama; desi wahyuni (Program Studi Hukum Ekonomi Syari'ah, 2026)
The profit-sharing system between landowners and durian orchard cultivators in rural areas is often conducted traditionally without written contracts, raising questions regarding fairness and its conformity with the principles of Islamic economic law. This study aims to analyze the practice of the profit-sharing system in Kedaloman Village, Gunung Alip District, Tanggamus Regency, and to assess the extent to which the practice reflects values of justice and sharia principles. The research employs a descriptive qualitative approach, with data collected through observation and in-depth interviews with cultivators and landowners. The findings indicate that the profit-sharing system is based on verbal agreements, with varying distribution patterns such as 50:50 or 60:40, depending on the cultivators’ contributions. This practice operates harmoniously on the basis of trust and local wisdom, although it has not fully complied with sharia principles such as contractual clarity, documentation, and transparency. The study also reveals that limited understanding of Islamic economic concepts and the strong influence of tradition serve as obstacles to the formal implementation of sharia-based systems. Therefore, education and assistance are needed in drafting written cooperation contracts based on the principles of justice, transparency, and voluntary agreement from the perspective of Islamic economic law.